Análise de cenários para melhorias do sistema de abastecimento de água do município de Abaetetuba (PA) por meio de simulação computacional - BATISTA, Maycon de Souza (2022)
In this study three proposed scenarios of the distribution network of the municipality of Abaetetuba-PA were analyzed, using simulation as a tool, after its hypothetical expansion. The work was divided into three steps, the first extends to obtaining data about the characteristics of the study area, then the second step which is characterized by computer modeling, which would be the insertion of the data obtained in the program, and finally using the EPANET 2.0 software, 24-hour dynamic simulation was performed in the three scenarios identifying the network pressure regions considered critical below the standard NBR 12218/2017 that regulates and establishes the minimum and maximum pressure limits. This method enabled interventions to be listed that could generate improvements in the operation of the water supply network, as well as assist in the decision making of the utility responsible for the system. The first scenario showed the expanded network without any intervention, after analysis it was found that the network served only 23,43% of the areas with pressure within the norm at peak consumption times. In scenario 2, elevated reservoirs were implemented, demonstrating efficiency of 91,45% after analyzing the pressures. Finally, in scenario 3, pressurizing stations were inserted to normalize the pressures that were in disagreement with the norm. After the insertion of the equipment, 83,79% of the pressures presented improvement. Thus, scenario 2 offered the best technical option, since it showed an improvement of 91,45% in the pressures of the distribution network.